(untitled) (Stamford Journal of Pharmaceutical Sciences, 2009)
In the present study, the antioxidant and analgesic potential of the 80% methanol extract of the leaves of Curcuma alismatifolia Gangnep was evaluated. The extract was investigated for its antioxidant activity using lipid peroxidation, total antioxidant capacity and reducing power assays. The extract showed significant antioxidant activities in lipid peroxidation assay compared to the standard antioxidant in a dose dependent manner. In lipid peroxidation assay, the IC50 value was found to be 122.43Î¼g/mL while the IC50 value for the reference ascorbic acid was 147.87Î¼g/ml. Moreover, Curcuma alismatifolia extract showed strong total antioxidant capacity and good reducing power. The analgesic activity was evaluated for its central and peripheral pharmacological actions using tail immersion method and acetic acid-induced writhing test in mice respectively. The extract, at the dose of 250 and 500 mg/kg, produced a significant (p < 0.05-0.001) increase in pain threshold in tail immersion methods in a dose dependent manner. In acetic acid-induced writhing test the extract, at a dose of 500 mg/kg, showed a maximum of 60.5% inhibition (p < 0.001) of writhing reaction compared to the reference drug diclofenac-sodium (75.0%). All experimental results suggest the use of this plant for the treatment of pain and inflammatory disorder. Key Words: Curcuma alismatifolia, Antioxidant, Lipid peroxidation, Total antioxidant capacity, Reducing power, Analgesic, Tail immersion. doi:10.3329/sjps.v1i1.1779 S. J. Pharm. Sci. 1(1&2): 3-9